Neomyth and Deconstruction: the Courtly Narrative and its Transformation in John Updike’s «Brazil» - Gonchar-Khanjyan, Natalie (Bulletin of Yerevan University B: Philology, 2025)
This article examines John Updike’s «Brazil» (1994) as a postmodern transformation of the Tristan and Isolde myth within the framework of magical realism and postcolonial discourse. The study hypothesizes that Updike does not reproduce the canonical narrative, but deconstructs it, presenting courtly love as resistance to societal norms, racial hierarchy, and gender constraints. The aim is to analyze how the novel reconfigures key mythopoetic elements–archetypes, sacred objects, ritual, and liminal space–through narrative inversion and symbolic reinterpretation. Particular attention is given to onomastic symbolism, the theme of embodiment and initiation, and the replacement of medieval ethics with contemporary identity politics. The methodological approach combines hermeneutics, structuralism, and postcolonial theory, alongside tools from comparative mythology and literary semiotics. The article argues that «Brazil» functions as a neomyth – a syncretic philosophical parable where the miraculous emerges not from divine intervention but from the human capacity to transgress. In reimagining the legend through a poetic of hybridity and transformation, Updike’s novel challenges traditional conceptions of love, fate, and the heroic, revealing how myth adapts to modern cultural and historical contexts.